Antimicrobial susceptibility and oxymino-β-lactam resistance mechanisms in Salmonella enterica and Escherichia coli isolates from different animal sources - Clemente, Lurdes (2020)
These results were partially presented at the 3rd ASM Conference on Antimicrobial Resistance in Zoonotic Bacteria and Foodborne Pathogens in Animals, Humans and the Environment, 26e29 June 2012, Aix-la-Provence and at TEMPH (Trends in Environmental Microbiology for Public Health), 18e21 September 2014, Lisbon.